Insights into the reactivity and lithium plating mechanisms of ultra-thin metal oxide coatings for anode-free solid-state lithium metal batteries - Counihan, Michael J.; Kim, Taewoo; Pathak, Rajesh; Zagorac, Teodora; Yang, Yingjie; Burns, Meghan E.; Cabana, Jordi; Klie, Robert F.; Hanley, Luke; Connell, Justin G.; Mane, Anil U.; Elam, Jeffrey W.; et al. (Frontiers in Batteries and Electrochemistry, 2023)
Solid-state batteries (SSBs) in an “anode-free” cell format using lithium metal anodes are the best candidates for high energy density battery applications. However, low lithium metal Coulombic efficiency and charge loss due to solid electrolyte interphase (SEI) formation severely limit the cycle life of anode-free SSBs. Here, we explore ultra-thin (5–20 nm) Al2O3 and ZnO coatings deposited by atomic layer deposition (ALD) on copper electrodes for anode-free cells with a solid polymer electrolyte. Voltammetry shows that lithium inventory loss from SEI formation is reduced over 50% with Al2O3@Cu electrodes, but these electrodes experience orders of magnitude higher interface resistances than bare Cu and ZnO@Cu electrodes due to low ionic and electronic conductivities. The electrochemical differences are reflected in XPS, where Al2O3 undergoes a self-limiting lithiation reaction with Li0, while ZnO reacts completely with Li0 to form LiZn and Li2O. These chemical differences result in higher and lower lithium plating nucleation overpotentials for Al2O3 (up to 220 mV) and ZnO (down to 15 mV) coatings, respectively, relative to uncoated Cu electrodes (35 mV). ToF-SIMS reveals lithium plating underneath a LiyAlOx coating and through emergent defects and pinholes with Al2O3@Cu electrodes, while it plates exclusively on top of converted ZnO@Cu electrodes. SEM corroborates these mechanisms, showing sparse coverage of isolated Li clusters plated with Al2O3@Cu electrodes, while Cu and ZnO@Cu grow more dense and interconnected deposits. Despite both coatings improving different aspects of anode-free battery design, unmodified Cu electrodes show higher Coulombic efficiencies (∼77%) than Al2O3@Cu (up to 70%) and ZnO@Cu (up to 75%) electrodes. Increasing Al2O3 thickness decreases the practical current density compared to unmodified Cu (30 µA/cm2), but increasing ZnO thicknesses can double or triple this value. These (electro)chemical and morphological observations suggest two mechanisms: less-reactive metal oxides develop lithium ion conductivity through their structure to plate lithium underneath, while more-reactive metal oxides undergo full reduction and conversion with lithium plating above the coating. This fundamental research opens future work to leverage these mechanisms and explore other materials for high-efficiency anode-free SSBs.